Analysis of time varying response on uptake patterns of Cu and Zn ions under application of ethylene diamine disuccinic acid and gibberellic acid in Lolium perenne. (December 2020) - Borker, Aditi R.; David, Karine; Singhal, Naresh
Abstract: The present study explores the effect of ethylene diamine disuccinic acid (EDDS) and gibberellic acid (GA) application on the phytoextraction of copper and zinc ions by Lolium perenne . When Cu was individually applied, accumulation diminished over time with little translocation from roots to shoots. In contrast, Zn accumulation and damage to roots rapidly increased over 3 days with increase in Zn translocation to shoots. Co-application of Zn to Cu amended treatments enhanced Cu concentration in shoots. For the CuEDDS application, EDDS significantly increased Cu accumulation and the damage to root increased over time, while gibberellic acid applied with Cu and Zn generally lowered metal uptake and decreased cell membrane damage. The application of EDDS and GA-EDDS, by themselves or with Cu and Zn, lowered transpiration and increased translocation, while GA increased transpiration but decreased translocation. EDDS application typically increased metal ion uptake by causing more cell damage, while GA typically lowered the damage and decreased metal uptake even though the transpiration increased over time and plant growth occurred. Furthermore, the behaviour of metal uptake changed over time and, for some treatments, the short-term and long-term response differed greatly. These results show that EDDS can be successfully used in phytoextraction of both Cu and Zn ions by Lolium perenne while GA can resist damage and protect against plant stress. Graphical abstract: Image 1 Highlights: Damage to root membrane barriers by EDDS increases Cu accumulation over time. GA can increase stress and damage over short time duration or ameliorate stress and influence plant recovery. GA-EDDS can either increase or decrease Cu and Zn uptake with GA reducing stress and EDDS increasing stress and damage. Exposure time can strongly influence uptake patterns of Cu and Zn in phytoextraction experiments. Complexation of EDDS with Cu and Zn mixture can trigger a reduction in copper and zinc transported to shoots.